Use of surface waves for ground characterization via linear elastic inversion method - Tan, Pei Sze. (2010)
Shear wave velocity profile provides information of the stiffness characteristics of the soil stratification. The shear wave velocity profile can be obtained using surface wave method. Surface wave methods as compared to the commonly used borehole methods allow one to determine the soil profile non-invasively. In this project, the underlying soil profile is obtained using surface wave dispersion curve via the linear elastic inversion method. Data such as the borehole log and dispersion curves are collated from various literatures. The obtained data are then used to perform the linear elastic inversion exercise. From the results of the inversion exercise, a method is developed to obtain an accurate soil profile. This method is furthered evaluate with other case studies. It is concluded that the linear elastic inversion method is able to provide reliable and accurate soil profiles. The study showed that the best agreement between the inverted soil profile and actual soil profile is given for the linear elastic data, followed by the finite element data and lastly the in-situ data. Results also showed that a RMS error of less than 1.5 for the matching of the synthetic and actual dispersion curves is able to provide a soil profile which is within ±20% of the actual soil profile.